Dynamic characteristics of a hydro‐turbine governing system considering draft tube pressure pulsation. Issue 7 (16th April 2020) - Guo, Pengcheng; Zhang, Hao; Gou, Dongming
Abstract : Hydropower takes on many tasks such as peak regulation and frequency modulation in the power system. In the actual operation process of the hydro‐turbine governing system, there is a certain degree of pressure pulsation in the draft tube. When the system is under unrated operating conditions, the draft tube pressure pulsation is more intense, and its dynamic behaviour becomes more complicated. In this study, the draft tube pressure pulsation is introduced into the dynamic model of the hydro‐turbine governing system, and its influences on the transient characteristics of the system are analysed under unrated conditions and rated conditions. The authors find that compared with the rated conditions, the draft tube pressure pulsation under unrated conditions has more significant effects on the transient characteristics of the system. A damped frequency of pressure pulsation is proposed in this study which provides an efficient method of regulating the dynamic behaviour of the system in real operation. All these findings are expected to be helpful for further study of the influence of pressure pulsation on transient characteristics of hydropower systems and improving their dynamic characteristics under operating conditions.